The positive relationship between androgen receptor splice variant-7 expression and the risk of castration-resistant prostate cancer: A cumulative analysis - Zhao, Shankun; Liao, Jian; Zhang, Shilong; Shen, Maolei; Li, Xin; Zhou, Libo (Frontiers in Oncology, 2023)
Background: At present, androgen deprivation therapy (ADT) is still the standard regimen for men with metastatic and locally advanced prostate cancer (PCa). The level of androgen receptor splice variant-7 (AR-V7) in men with castration-resistant prostate cancer (CRPC) has been reported to exceed the baseline in those with hormone sensitive prostate cancer (HSPC). Aim: Herein, we managed a systematic review and cumulative analysis to evaluate whether the expression of ARV7 was significantly higher in CRPC patients. Methods: The common-used databases were conducted to identify the potential studies concerning the level of the AR-V7 in CRPC patients. The association between CRPC and AR-V7-positive was pooled by using the relative risk (RR) with the corresponding 95% confidence intervals (CI) under a random-effects model. For detecting the potential bias and the heterogeneity of the included studies, a sensitivity analysis was performed. Publication bias were assessed via both of the Egger’s and the Begg’s tests. This study was registered on PROSPERO (ID: CRD42022297014). Results: This cumulative analysis included 672 participants from seven clinical trials, among which 318 were HSPC patients, and 354 were CRPC patients. Based on the fixed-effects model, pooled results showed that the expression of AR-V7 positive was significantly higher in men with CRPC when compared those with HSPC (RR = 7.55, 95% CI: 4.61-12.35, P< 0.001). In the sensitivity analysis, the combined RRs did not change substantially, with a range from 6.85 (95%CI: 4.16-11.27, P < 0.001) to 9.84 (95%CI: 5.13-18.87, P < 0.001. There was no significant publication bias detected in this study. Conclusion: Evidence from the seven eligible studies demonstrated that male patients with CRPC had a significantly elevated positive of AR-V7. More researches are still warranted to clarify the relation between CRPC and the AR-V7-positive.